Microplastics-Assisted Campylobacter Persistence, Virulence, and Antimicrobial Resistance in the Food Chain: An Overview - Irene Ortega-Sanz; Andreja Rajkovic (Foods)
Recent studies have detected microplastics (MPs) in seafood and various food products worldwide, including poultry, fish, salt, beverages, fruits, and vegetables. This widespread contamination makes human exposure through consumption unavoidable and raises concerns for food safety and human health. MPs provide physical support to microorganisms for biofilm formation, protecting them from extreme conditions and facilitating their persistence in the environment. However, little is known about the impact of MPs in the transmission of foodborne pathogens and subsequent spread of infectious diseases like campylobacteriosis, the most common foodborne illness caused by a bacterium, Campylobacter. This review explores the sources of MP contamination in the food chain and offers a comprehensive overview of MP presence in animals, food products, and beverages. Moreover, we compile the available studies linking MPs and Campylobacter and examine the potential impact of these particles on the transmission of Campylobacter along the food chain with a particular focus on poultry, the main source and reservoir for the pathogen. While the environmental and toxicological effects of MPs are increasingly understood, their influence on the virulence of Campylobacter and the spread of antimicrobial resistance remains underexplored. Further studies are needed to develop standardized methods for isolating and identifying MPs, enabling comprehensive investigations and more effective monitoring and risk mitigation strategies.